New Business Model Generation of E-Money for Online Payment: A Case Study of XL Tunai an E-Money Product of PT XL Axiata, Tbk - Koesmanggala, Koesmanggala; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2015)
Abstract.As second largest Mobile Network Operator in Indonesia, with over 65 million subscriber base, PT XL Axiata Tbk (XL) intends to strengthen its position in the market, by introducing a diversified service through offering of electronic money (e-money) as payment method, named as XL Tunai. After over two years since the service was launched on 2012, both of adoption and usage rate is still below initial expectation. Although there is some argument that the business does not well take off due to some constraints from the regulations side, it is believed that customers do not find strong reason to use of XL Tunai as payment method.This research is intended to analyze, formulate and suggest implementation of strategies that are realized through new business models for the e-money services with specific application as online payment method. A conceptual framework used to perform this research derives from combination of strategy tools namely: PEST, Porter’s Five Forces, VRIO Framework, Value Chain Analysis, SWOT analysis, that are used to analyze the business case, while strategy formulation is developed using TOWS Matrix, business and corporate level strategy formulation with main focus of diversification framework adopted from Hamel-Prahalad’s core competencies and market matrix. Four generated business models referring to the diversification roadmap are then interpreted in nine business models building blocks written on Osterwalder – Pigneur’s Business Model Canvas.Keywords: business model generation, business model canvas, e-money